Anidulafungin: a novel echinocandin. Issue 1 (January 2006) - Vazquez, Joséé A
Fungal infections have emerged as a major cause of morbidity and mortality in an immunocompromised host. Until recently, the available treatment for serious fungal infections comprised either amphotericin B or azoles, which have limitations. The development of the echinocandins, including caspofungin and micafungin, has helped to fill the need for more efficacious antifungals that are broad spectrum, useful across different patient populations and have a good safety profile. Anidulafungin is the newest of the echinocandins under development for the treatment of mucosal and systemic fungal infections. Anidulafungin has demonstrated potent in  vitro activity against Aspergillus and Candida spp., including those strains that are resistant to either fluconazole or amphotericin B. Results of several clinical trials show that anidulafungin is effective in treating esophageal candidiasis, candidemia and invasive candidiasis. In addition, studies evaluating the concomitant use of anidulafungin and either amphotericin, voriconazole or cyclosporin did not show clinically significant drug––drug interactions or altered adverse event profiles. A population kinetics analysis showed no significant effect of age, race, concomitant medications and renal or hepatic insufficiency on the population kinetic properties of anidulafungin. The efficacy and safety profile of anidulafungin, combined with its unique pharmacokinetic characteristics, make it a suitable alternative antifungal compound for first-line therapy of candidemia as well as mucosal, systemic and antifungal-refractory candidiasis.